Application of a CC-VSI for Active Filtering and Photovoltaic Energy Conversion with a 1-to-1 MPPT controller - Tumbelaka, Hanny H.; Miyatake, Masafumi (Jurnal Teknik Elektro, 2008)
This paper focuses on the implementation of a three-phase four wire current-controlled Voltage Source Inverter (CC-VSI) as both PV energy extraction and power quality improvement. For power quality improvement, the CC-VSI works as a grid current-controller shunt active power filter. Then, the PV array supported by a Look-up Table type of a MPPT controller is coupled to the DC bus of the CC-VSI. The output of MPPT controller is a DC voltage that determines the DC-bus voltage according to the PV maximum power. The computer simulation results show that the system works properly in steady state and dynamic condition.